Immigration, fertility, and human capital: A model of economic decline of the West - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2010)
I show how the influences of unskilled immigration, differential fertility between immigrants and the local indigenous population, and incentives for investment in human capital combine to predict the decline of the West. In particular, indigenous low-skilled workers lose from unskilled immigration even if the indigenous low-skilled workers do not finance redistribution, do not compete with immigrants in the labor market, and do not compete with immigrants for publicly financed income transfers. For the economy at large, high-fertility unskilled immigrants and a low-fertility indigenous population result in economic decline through reduced human capital accumulation and reduced growth of per-capita output.
Keywords: D30; F22; J10; O40; 330; immigration; redistribution; ethnic diversity; fertility; human capital; economic growth; Einwanderung; Ungelernte Arbeitskräfte; Migranten; Fruchtbarkeit; Bevölkerung; Bildungsinvestition; Einkommensumverteilung; Stagnation; Theorie; Westliche Staaten